PENGGUNAAN MODEL PEMBELAJARAN PROBLEM POSING TIPE PRE-SOLUTION DALAM PENINGKATAN HASIL BELAJAR FISIKA - Yola Allan Sembiring; Sabar Pirnando Pardosi (Jurnal Dinamika Pendidikan, 2016)
The objective of the present study is to fid out the effect of implementation of problem posing approach on the students’learning outcome in Physics. The study was conducted in SMAN I Klapanunggal Bogor at academic year 2014/2016. There were 10th grade students as the sample of the study, selected through cluster random sampling. The data were gathered by using a test. Data analysiswas done by using t -test. The results of the study have revealed that problem posing approach effectedthe students’ learning outcome in Physics. The test results indicate normality test results Lilliefors Lrithmetic = 0.1338 > 0.1401 = Ltabel usingsignificance level = 0.05, which means the normal distribution of data, as well as test results show the homogeneity using Hartley test results Frithmetic = 1.20 < 2.61 = Ftabel, which means that both the data homogeneous. While testing the hypothesis by using t tests obtained tarithmetic = 7.94 > 2.72 = ttabel using a significance level of = 0.05, this means accept Ha.Keywords : Problem-Solution Posing Pre types, Learning Outcomes, dynamic electricity